Influence of obesity and overweight on transforming growth factor beta 1 levels and other oxidative and cardiometabolic parameters - Ottobelli Chielle, Eduardo; Muller Ogliari, Vanieli Cristina; de Carvalho, Diego; Pertile Remor, Aline (Clinical and Biomedical Research, 2018)
Introduction: Obesity is associated with the development of metabolic disorders that can be diagnosed through inflammatory and oxidative biomarkers. Background: This study evaluated the influence of obesity and overweight on serum concentrations of vitamins C and E, transforming growth factor beta 1 (TGF-β1) and cardiometabolic parameters. Methods: A cross-sectional study was conducted with 169 participants (24 normal weight, 16 overweight and 129 obese). Anthropometric measures and concentrations of vitamins C and E, thiobarbituric acid reactive substances (TBARS), TGF-β1, lipid profile, glycated hemoglobin (HbA1c), glucose and insulin were determined, and homeostatic model assessment of insulin resistance (HOMA-IR) and insulin sensitivity (IS) were calculated. Results: Obese and overweight participants showed significantly higher levels of TGF-β1, vitamin E, insulin, HbA1c, glucose, cholesterol, low-density lipoprotein cholesterol (LDL-c), triglycerides, HOMA-IR, and TBARS compared with normal weight patients, associated with a significant reduction in IS, high-density lipoprotein cholesterol (HDL-c), and vitamin C. Conclusion: Obesity and overweight may lead to significant changes in TGF-B1, biochemical and oxidative markers. Increased levels of TGF-β1 may promote inflammation and interfere with IS. Reduced concentrations of vitamin C and increased levels of TBARS led to a redox imbalance in obese and overweight patients, suggesting that vitamin E is not a promising oxidative biomarker since it is lipophilic and its concentration is influenced by body fat. These results may help determine the oxidative and inflammatory pathways related to obesity and its comorbidities. Keywords: Obesity; vitamins; antioxidants; metabolism